A process to evaluate an iTV platform to enhance seniors' access to information about public and social services. Issue 4 (16th November 2018) - Silva, Telmo; Caravau, Hilma; Reis, Liliana; Campelo, David
Abstract : Purpose: The purpose of this paper is to present a process to evaluate the usability and usefulness of a high-fidelity prototype of the +TV4E platform (removed for blind review), an iTV service which aims to promote the info-inclusion and quality of life of Portuguese seniors by delivering informative contents about public and social services. Design/methodology/approach: The research presented in this study is qualitative and uses an inclusive and participatory co-design process involving seniors to evaluate usability of an iTV service with support of the Post-Study System Usability Questionnaire (PSSUQ) tool and a questionnaire survey. The participants were 11 individuals, over 65 years enrolled in an adult day care center in Aveiro city, Portugal (removed for blind review). Findings: Findings from this study allowed to assess some key aspects in the +TV4E platform implementation that should be addressed in its final version. Using the PSSUQ tool as well as a questionnaire survey confirmed the relevance of this platform to meet seniors' informational needs. Originality/value: This original research offers insights on how valuable is including potential users in the development and test phases of an innovative technology which intends to offer more adequate tools to improve seniors' info-inclusion and quality of life. Also, it is possible to understand what should be considered when evaluating a prototype intended to be used by seniors.